Postulation of General Unions of Lines and Multiplicity Two Points in ℙ3. (23rd March 2014) - Ballico, E.
Abstract : We prove that a general union X ⊂ ℙ 3 of prescribed numbers of lines and double points has maximal rank, except a few well-known exceptional cases.